Analisis Sistem Informasi Akuntansi Penggajian dan Efektivitas Pengendalian Intern pada Restoran - Suryanti, Ery; Lesmana, Hendra; Utami, Bernadette Cahya Putri; Zulfa, Puspa Fortuna (ProBisnis : Jurnal Manajemen, 2025)
The research with the intention of knowing how the payroll system and internal control in the West Java branch restaurant, the procedures in this restaurant already have a very good system starting from supporting data and evidence of existing transactions and documents owned are very complementary to activities in the payroll system. The analysis technique in this study is descriptive analysis, namely by analyzing according to the existing data then being able to describe and compare data from the company so that it can be supporting data for research. Researchers also conducted interviews, observations and to complete the data, a literature study was carried out in accordance with the research. The results of the study are that in this company the data is very supportive in the accounting information system starting from records then supporting data so that the payroll system runs smoothly and the effectiveness of internal control in this internal control system has also run effectively, each employee works well and honestly, this internal control system is also carried out directly by the head office so that when there are problems or obstacles that occur, they can be resolved immediately because with internal control running well, the company is in good.